Second Five Year Plan Programme for 1960-61 Andaman and Nicobar Administration - Government of Andaman and Nicobar (Government of Andaman and Nicobar Islands, 1960)
The Second Five-Year Plan (1960-61) for the Andaman and Nicobar Islands presents a comprehensive development strategy focusing on agriculture, infrastructure, social welfare, and economic enhancement, with a total outlay of Rs. 610.135 lakhs. Key priorities include the expansion of coconut plantations, low-income housing schemes, transport and communication improvements, and the development of minor ports. Sector-specific initiatives target veterinary services, poultry farming, seed multiplication, fisheries mechanization, and dairy and timber production, aiming to boost local productivity and employment. Educational development is emphasized through the conversion of primary schools into junior basic schools, establishment of senior and vocational schools, scholarships, and teacher recruitment. Health and sanitation improvements include hospitals, dispensaries, anti-malarial campaigns, and rural water supply projects. Infrastructure development encompasses road construction, police facilities, staff housing, and community development blocks, alongside initiatives for tribal welfare and forest management. The plan reflects progressive financial management through supplementary grants, re-appropriations, and monitoring of revenue from projects, ensuring adaptability to evolving fiscal and developmental needs. Overall, the 1960-61 plan seeks to elevate living standards, promote sustainable economic growth, and strengthen institutional capacity, laying a structured foundation for the socio-economic advancement of island communities.
Andaman and Nicobar Administration
Andaman and Nicobar Administration
Keywords: Andaman And Nicobar Islands; State Plan; Agricultural Development; Infrastructure Expansion; Social Welfare; Housing Schemes; Fisheries Development; Education Initiatives; Health Infrastructure; Forest Management; Budget Allocation; Community Development